A new result on recovery sparse signals using orthogonal matching pursuit - Chen, Xueping; Liu, Jianzhong; Chen, Jiandong (Statistical theory and related fields, 2022)
Orthogonal matching pursuit (OMP) algorithm is a classical greedy algorithm widely used in compressed sensing. In this paper, by exploiting the Wielandt inequality and some properties of orthogonal projection matrix, we obtained a new number of iterations required for the OMP algorithm to perform exact recovery of sparse signals, which improves significantly upon the latest results as we know.